IMPLIKASI HUKUM TERHADAP PENGHAPUSAN SISTEM ALIH DAYA PADA PERUNDANG-UNDANGAN KETENAGAKERJAAN - Kantikha, I Made; Harahap, Pardamean; Muchtar, Andhyka; Hendrani, Ai; Sherill, Fredrika; Aurelia Shabilla, Reysha; Daishahwa, Daishahwa; Fritiana, Anesya; Hadi Putra, Albert (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research examines the legal implications of eliminating the outsourcing system in Indonesian labor law amid ongoing debates post-Job Creation Law. The objective is to analyze impacts on worker protection, business legal certainty, and state regulatory roles. Employing normative juridical methods with statute and conceptual approaches, supplemented by empirical data, the population comprises outsourcing workers, practitioners, and employers in Tangerang Regency, using purposive sampling of experienced respondents. Instruments include semi-structured interviews and structured questionnaires, analyzed via qualitative descriptive techniques with data triangulation. Findings reveal outsourcing enhances business efficiency but causes job insecurity, wage disparities, and tripartite supervision challenges. Conclusions recommend comprehensive transitional regulations over 2-3 years, BPJS strengthening, and bipartite supervision reforms to balance interests without mass layoffs or economic instability.